2019
DOI: 10.1016/j.jsbmb.2019.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Estrogens and breast cancer: Mechanisms involved in obesity-related development, growth and progression

Abstract: Obesity is a risk factor for estrogen receptor-positive (ER+) breast cancer after menopause. The pro-proliferative effects of estrogens are well characterized and there is a growing body of evidence to also suggest an important role in tumorigenesis. Importantly, obesity not only increases the risk of breast cancer, but it also increases the risk of recurrence and cancer-associated death. Aromatase is the rate-limiting enzyme in estrogen biosynthesis and its expression in breast adipose stromal cells is hypoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
131
2
16

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(150 citation statements)
references
References 200 publications
(203 reference statements)
1
131
2
16
Order By: Relevance
“…The effects of estrogens proliferation help the growth of body is evidence of the important role in tumor genesis. Importantly, obesity not causes breast cancer, but it associated with other factors such as loco-regional recurrence, metastasis of axillary nodes and cancer-associated death [15] Also, Picon-Ruiz and colleagues carried a study between 2011 and 2014, in the United States, and reported that, obesity had been associated with premature menopause and premature menopause increased the risk of breast cancer [16] . Guldberg and colleagues also revealed that, premenopausal breast cancer women who are overweight and have poorer physical function have poorer prognosis [17] .…”
Section: Chakraborty Et Al Reported Results Of 426 Patients With Bcmentioning
confidence: 99%
“…The effects of estrogens proliferation help the growth of body is evidence of the important role in tumor genesis. Importantly, obesity not causes breast cancer, but it associated with other factors such as loco-regional recurrence, metastasis of axillary nodes and cancer-associated death [15] Also, Picon-Ruiz and colleagues carried a study between 2011 and 2014, in the United States, and reported that, obesity had been associated with premature menopause and premature menopause increased the risk of breast cancer [16] . Guldberg and colleagues also revealed that, premenopausal breast cancer women who are overweight and have poorer physical function have poorer prognosis [17] .…”
Section: Chakraborty Et Al Reported Results Of 426 Patients With Bcmentioning
confidence: 99%
“…After menopause, adipose tissue is the primary source of estrogen production in the body. 6 Adipose tissue interconverts stored or circulating sex steroids but does not synthesis sex steroids de novo. Circulating C19 steroid precursors androstenedione, dehydroepiandrosterone (DHEA) and DHEA-sulphate (DHEA-S) act as a reservoir for extragonadal estrogen synthesis.…”
Section: Adipose-derived Estrogens and Pahmentioning
confidence: 99%
“…4 After menopause, the adipose tissue, including that of the breast, is the main site of estrogen production. 5,6 Estrogens are also synthesized in the bone, joints, and brain. 5 In these women, aromatase inhibitors are effective at suppressing aromatase throughout the body, thus profoundly decreasing estrogen levels both locally and systemically.…”
Section: What Is Endocrine Therapy?mentioning
confidence: 99%
“…Candidates include insulin and glucose, as well as inflammatory mediators and estrogens produced locally in the breast adipose tissue. 6,[66][67][68] Some tumors rely heavily on glucose as a source of energy and, as a result, display enhanced glucose uptake and metabolism. 69 This is the basis of 18 F-fluorodeoxyglucose positron emission tomography, whereby a non-metabolizable glucose tracer is used to image cancer metastases.…”
Section: Are There Consequences Of Diabetes and Bone Loss On Risk Ofmentioning
confidence: 99%